P1768 The value of global longitudinal strain in non-alcoholic steatohepatitis-associated cirrhosis. (17th January 2020) - Dimitroglou, Y; Aggeli, C; Alexopoulou, A; Alexopoulos, T; Nitsa, A; Apostolou, I; Patsourakos, D; Vasilieva, L; Dourakis, S P; Tousoulis, D
Abstract: Introduction: Non-alcoholic steatohepatitis (NASH) in patients with metabolic syndrome is a common cause of cirrhosis and has been associated with increased cardiovascular mortality. In patients with liver cirrhosis systolic or diastolic dysfunction can be observed and is independent of the cirrhosis etiology. Only few studies using newer echocardiography indices such as Global Longitudinal Strain (GLS) have been published in cirrhotic patients. Purpose: To evaluate GLS in patients with NASH cirrhosis when compared to other etiologies. Methods: A total of consecutive 36 cirrhotic patients aged 18-70 were included in our study. Standard speckle-tracking software was used for offline analysis of standard apical views and GLS was calculated. Stroke Volume Index (SVI) was calculated with the Simpson method and a standard 2D, Doppler and Tissue Doppler examination was performed in all patients. Results: Median age of the study population was 58 (IQR 50-64) years, 78% were male and 17% had ascites. Cirrhosis was considered decompensated in 21 (58%) of patients. The 28%, 42% and 19% had NASH-associated, alcoholic and viral etiology of cirrhosis, respectively. Median ejection fraction (EF) was 60% (IQR: 57%; 65%) and GLS was -21.1% (-19.7%; -23.1%) in the total population. Absolute value of GLS was lower in patients with NASH cirrhosis compared to other etiologies (p = 0.009) (figure 1). EF, SVI, left atrial volume index (LAVI), E/e' ratio and mitral annular velocity (e') did not differ significantly between those with NASH associated cirrhosis and the rest. GLS values were significantly correlated with EF (r=-0.588, p = 0.002), SVI (r=-0.469, p = 0.016) and BNP levels (r=-0.571, p = 0.007), but not with age, left ventricular end diastolic volume, left atrial volume index, E/e', mitral annular velocity and blood pressure. According to a multivariable linear regression model, NASH etiology [B = 2.1 (0.6; 3.7), p = 0.008)] and EF (per 10% increase) [B=-1.7 (-3.3; -0.2), p = 0.03)] were the only independent factors associated with GLS values in cirrhotic patients. Conclusions: GLS values are within normal limits in cirrhotic patients but seem to be affected in patients with NASH associated cirrhosis. Further studies are needed to assess the prognostic implications of this finding.